Management and outcome of TaG3 tumours of the urinary bladder in the nationwide, population-based bladder cancer database Sweden (BladderBaSe). (4th July 2019) - Jahnson, Staffan; Gårdmark, Truls; Hosseini, Abolfazl; Jerlström, Tomas; Liedberg, Fredrik; Malmström, Per-Uno; Rosell, Johan; Sherif, Amir; Ströck, Viveka; Häggström, Christel; Holmberg, Lars; Aljabery, Firas
Abstract: Purpose: To investigate the management of TaG3 tumours of the urinary bladder using nationwide population-based data in relation to the prevailing guidelines, patients' characteristics, and outcome. Materials and methods: The Bladder Cancer Data Base Sweden (BladderBaSe), including data from the Swedish National Register for Urinary Bladder Cancer (SNRUBC), was used to study all patients with TaG3 bladder cancer diagnosed from 2008 to 2014. Patients were divided into the following management groups: (1) transurethral resection (TUR) only, (2) TUR and intravesical instillation therapy (IVIT), (3) TUR and second-look resection (SLR), and (4) TUR with both SLR and IVIT. Patient and tumour characteristics and outcome were studied. Results: There were 831 patients (83% males) with a median age of 74 years. SLR was performed more often on younger patients, on men, and less often in the Western and Uppsala/Örebro Healthcare regions. IVIT was performed more often with younger patients, with men, in the Western Healthcare region, and less often in the Uppsala/Örebro Healthcare region. Death from bladder cancer occurred in 6% of cases within a median of 29 months (0–84 months) and was lower in the TUR/IVIT and TUR/SLR/IVIT groups compared to the other two groups. Conclusion: In the present study, there was, according to the prevailing treatment guidelines, an under-treatment with SLR for older patients, women, and in some healthcare regions and, similarly, there was an under-treatment with IVIT for older patients. Cancer-specific survival and relative survival were lower in the TUR only group compared to the TUR/IVIT and TUR/SLR/IVIT groups.